Algorithms for Transforming Strings by Reversals - Teixeira, Gustavo da S.; Lintzmayer, Carla N. (Revista Eletrônica de Iniciação Científica em Computação, 2021)
A reversal is an operation that cuts a segment of a string and reverses it. The problem of Transforming Strings by Reversals (TSbR) consists of, given two strings, ﬁnding the minimum number of reversals that transform one string into the other. TSbR is NP-hard and there are not many algorithmic results for it. In this work, we propose eight practical algorithms for TSbR and compare them, experimentally